Sketch Engine Implementation in Arabic Vocabulary Learning - Ashfia, Ahmad; Mu’awanah, Elyatul; Nur, Abdullah; Susiawati, Wati (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2023)
This study aims to understand how to analyse the language corpus and be able to apply it properly and to improve the Arabic vocabulary of new students of UIN Jakarta majoring in Arabic Language Education (PBA) through the application of sketch engine. The application of sketch engine in learning Arabic vocabulary is still very rarely applied. This sketch engine is the first time applied to new students of UIN Jakarta in the special guidance of al-'Arabiyah al-Mukasyafah. The research method used is descriptive method with qualitative approach (field research). While data collection techniques are done by observation, interviews, and documentation. Based on the results of the study, there are three stages carried out; 1) presentation of conceptual material 2) presentation of skill material 3) evaluation of activities 4) reflection of activities. From these four stages, students are able to apply their applicative knowledge in using the sketch engine. All students who were divided into 4 groups were able to follow the steps of corpus analysis very well through reports in the form of working papers. In addition, the application of this sketch engine is able to increase students' Arabic vocabulary skills through finding word collocations and finding various meanings that fit the vocabulary.